+0  
 
0
59
1
avatar

1. Let f(x)=4x-7, g(x)=(x+1)^2, and s(x)=f(x)+g(x). What is s(3)?

2. Let f(x)=2x^2+3x-9, g(x)=5x+11, and h(x)=-3x^2 +1. Find f(x)-g(x)+h(x)

 Jan 30, 2021
 #1
avatar+116126 
+1

f(x)  = 4x  - 7

 

g(x)  =  x^2 + 2x +  1

 

f(x)  + g(x)   =     x^2  + 6x  - 6

 

So  s(3)   =     (3)^2  + 6(3)  -  6   =     21

 

 

Second one   ....add   like  you  normally would after aligning the  terms

 

2x ^2  +   3x    - 9

            +  5x   +11

-3x^2              + 1

_______________

-x^2    +  8x   + 3

 

 

cool cool cool

 Jan 30, 2021

56 Online Users

avatar
avatar